Computer forensics jumpstart - Solomon, Michael 1963- (Wiley Pub., 2011)
Annotation
Includes bibliographical references and index
Keywords: Computer security; Computer networks -- Security measures; Computer crimes -- Investigation; Forensic sciences; Computer Security; Forensic Sciences; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Criminalité informatique; Enquêtes; Criminalistique; forensic science; Computer crimes; Investigation; Computer networks; Security measures